Somnium [videorecording (Blu-Ray)] - Levine, Chloe; Van Dien, Grace, 1996-; Schaech, Johnathan, 1969- (Yellow Veil Pictures, 2025)
At experimental sleep clinic, Somnium, dreams are made real. Side effects may include: hallucinations, confusion, paranoia, sleep paralysis, detachment from reality, lost sense of self, permanent nightmares.